2021
DOI: 10.3390/ijerph182111102
|View full text |Cite
|
Sign up to set email alerts
|

Isotemporal Substitution Analysis of Accelerometer-Derived Sedentary Behavior and Physical Activity on Cardiometabolic Health in Korean Adults: A Population-Based Cross-Sectional Study

Abstract: Reducing sedentary behavior and increasing physical activity may be important for maintaining good cardiometabolic health. However, many studies have focused on the independent effect of sedentary behavior and physical activity, but it is unclear whether replacing time spent in sedentary behavior with physical activity is beneficial for cardiometabolic health. Therefore, this population-based cross-sectional study aimed to investigate the effect of behavioral transformations between sedentary behavior and leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This group consistently demonstrated lower ORs for MetS, regardless of sex, age, or subgroup classification. These results are consistent with previous studies highlighting the positive impact of regular physical activity on metabolic health [ 15 , 16 , 17 , 18 ]. The persistent association between regular physical activity and reduced risk of MetS underscores the significance of maintaining a consistent physical activity routine and transcending demographic boundaries.…”
Section: Discussionsupporting
confidence: 93%
“…This group consistently demonstrated lower ORs for MetS, regardless of sex, age, or subgroup classification. These results are consistent with previous studies highlighting the positive impact of regular physical activity on metabolic health [ 15 , 16 , 17 , 18 ]. The persistent association between regular physical activity and reduced risk of MetS underscores the significance of maintaining a consistent physical activity routine and transcending demographic boundaries.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that increasing MVPA and reducing SB in daily life are important. Our previous research suggested that replacing 30 minutes of SB with MVPA reduced the risk of cardiometabolic disease by 23% [ 18 ], indicating the need for public health interventions to meet MVPA and SB guidelines in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of wear was calculated by subtracting any non-wear duration of more than 60 consecutive minutes. Records with less than 10 hours of wear duration per day for four days were considered invalid [ 18 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple research studies have substantiated the positive impacts of physical exercise on mental well-being ( Dai and Menhas, 2020 ; Duncan et al, 2020 ; Saqib et al, 2020 ). Moreover, a positive correlation exists between increased levels of daily exercise, also known as habitual physical activity (HPA), and enhanced aerobic performance and an extended lifespan ( Ma et al, 2021 ; Welsner et al, 2021 ). Consistent participation in physical activity yields enhancements in both bodily and mental well-being, with the adoption of additional health-enhancing practices and reduced susceptibility to chronic ailments ( Saqib et al, 2020 ).…”
Section: Hypothesis Operationalizationmentioning
confidence: 99%